Cysteine-Rich Protein 61 (CCN1) Deficiency Alleviated Cardiac Remodeling in 5/6 Nephrectomized Mice by Suppressing the MAPK Signaling Pathway - Yihan Zhao; Liang Gu; Yunxuan Chen; Yibei Lin; Jincheng Xing; Diyan Xu; Zhen Su; Zhouqing Huang (Cardiovascular Therapeutics)
Conclusion: Our in vivo and in vitro study showed that specific CCN1 deficiency markedly alleviated cardiac remodeling in 5/6 Nx mice through the inhibition of the MAPK pathway.